PERANCANGAN IKLAN KAMPANYE PENGHARGAAN ADIWIYATA KABUPATEN GRESIK MELALUI ANIMATION EXPLAINER SEBAGAI UPAYA MENINGKATKAN KESADARAN LINGKUNGAN HIDUP - Ali, M Fauzil; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design campaign advertising Adiwiyata Gresik is to raise awareness of the environment in the school district. Further research was conducted using qualitative research methods that do interviews, observation, documentation, and literature to obtain the data used to support the manufacture of the design concept of the ad campaign. Data were analyzed using several stages, namely data reduction, data presentation, and conclusion. After analyzing the data, found a design concept or keyword advertising campaign is "Truly". Description of "Truly" is a being who really or actually owned. The concept of "Truly" aims to show that Gresik is the region that has the identity of environmentally education. That is, the concept of truly presented to instill public perception that environmentally education in Indonesia is Gresik. Results from the design ad campaign is to raise awareness on the environment and is expected to schools that have not received awards Adiwiyata compelled to care for the environment, so as to achieve the award Adiwiyata.Â Keywords: Advertising Campaign, Adiwiyata, Environment, Animation Explainer